2014
DOI: 10.1007/s10551-014-2421-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Individual Variables, Organizational Variables and Moral Intensity Dimensions in Libyan Management Accountants’ Ethical Decision Making

Abstract: This study investigates the association of a broad set of variables with the ethical decision making of management accountants in Libya. Adopting a cross-sectional methodology, a questionnaire including four different ethical scenarios was used to gather data from 229 participants. For each scenario, ethical decision making was examined in terms of the recognition, judgment and intention stages of Rest's model. A significant relationship was found between ethical recognition and ethical judgment and also betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
133
4
19

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(173 citation statements)
references
References 135 publications
17
133
4
19
Order By: Relevance
“…As Rest (1986) argued that all four stages were conceptually different and that success in one stage did not mean success in other stages, Johari et al (2011) identified significant positive relationships between the first three processes of ethical decision-making among auditors. Musbah et al (2016) reported a significant relationship between ethical recognition and ethical judgment and also between ethical judgment and ethical intention, but ethical recognition did not significantly predict ethical intention, and the same results were found in Haines et al’s (2008) research. Similarly, Jagger (2011) found that levels of ethical sensitivity had a significant impact on the development of moral judgment.…”
Section: Theoretical Framework and Hypothesessupporting
confidence: 60%
“…As Rest (1986) argued that all four stages were conceptually different and that success in one stage did not mean success in other stages, Johari et al (2011) identified significant positive relationships between the first three processes of ethical decision-making among auditors. Musbah et al (2016) reported a significant relationship between ethical recognition and ethical judgment and also between ethical judgment and ethical intention, but ethical recognition did not significantly predict ethical intention, and the same results were found in Haines et al’s (2008) research. Similarly, Jagger (2011) found that levels of ethical sensitivity had a significant impact on the development of moral judgment.…”
Section: Theoretical Framework and Hypothesessupporting
confidence: 60%
“…Theoretically, an individual's ethical orientation provides a guideline in shaping the individual beliefs, attitudes, and values used in dealing with ethical dilemmas (Hunt & Vitell, ; Musbah, Cowton & Tyfa, ). Empirical studies on ethical orientation explain a variety of decisions that individuals make in organizations (e.g., Henle, Giacalone & Jurkiwicz, ; Marques & Azevedo‐Pereira, ; Ismail, ).…”
Section: Theoretical Development and Hypotheses Formulationmentioning
confidence: 99%
“…Estes últimos resultados não são consistentes com os de outros autores (vide Musbah et al, 2016;Yang & Wu, 2009), que associam significativa e positivamente a tempestividade com as etapas da tomada de decisão ética de Rest (1986). Por outro lado, os resultados obtidos não replicam os de Barnett e Valentine (2004), que defendem pouca ou nenhuma associação da tempestividade com o processo de tomada de decisão ética.…”
Section: Resultsunclassified
“…Estes resultados contrariam os resultados de estudos anteriores (Chan et al, 2011;Forsyth, 1980Forsyth, , 1992Musbah et al, 2016). De notar que Musbah et al (2016) salientam que o idealismo foi considerado como a variável individual com mais influência na predição das três etapas do modelo de tomada de decisão ética de Rest (1986) nos contabilistas. Em sentido oposto, são os resultados obtidos por Jesus, Sarmento e Duarte (2017), que, recorrendo a uma metodologia distinta, concluem que os contabilistas têm uma visão utilitarista da ética.…”
Section: Resultsunclassified